Identification and analysis of factors influencing food advertisements on buying behaviour of children in emerging consumption markets: the case study of Afghanistan. (16th December 2019) - Azimi, Jawad; Claver, Jimbo H.; Suzuki, Takeru; Pascal, Jesus
This study assessed impact of food advertising on purchasing behaviour of children in emerging consumption markets. A case study was conducted in Kabul, Afghanistan. In this research, we considered a system where children's buying behaviour was the output and food advertising and moderator variables namely age, siblings, gender, parent's influence and media type were considered as inputs. The study relied on primary data collected from 385 children aged between 5 and 15. Data were analysed with STATA 2013. The data and statistical models were tested for validity and reliability; the tests included Cronbach's alpha, Jarque-Bera, Bruesch-Pagan/Cook-Wisberg, Winsorization, Skewness and Kurtosis, Akaike information criterion (AIC), and variance inflation factor (VIF). The study found that television advertisements had the most influence on purchasing behaviour of children directly or indirectly through their parents. The study also found that the magnitude of advertising outcome on children varied based on moderator variables mentioned above.